Neologism in Arabic Language: The Example of Al-Jazeera News Site - Emine Bağmancı; Abdulhakim Önel (Şarkiyat Mecmuası)
Language has changed from past to present in line with the unique developments of each period. In today’s rapidly changing conditions, this inevitable influence of language has become more visible. Linguistic mobility that started with the need to name new situations paved the way for the emergence and development of the concept of neologism. Since languages can’t stay away from this concept, they are expected to give importance to deriving words by their structures. Neologism, which is one of the main indicators of the vitality of the language, is of great importance as it allows us to put the internal dynamics of the language to work. Although neologism is a new linguistics subject, the theoretical basis for creating a new element in Arabic dates back to the early years of İslam. Studies that started with the effort to preserve the essence of the language as a result of the interaction with different nations have created an important infrastructure in this field. Nowadays, there is an intense flow of words transferred from English to Arabic due to its dominance in the technological field. In this context, it is possible to say that modern studies carried out within the scope of Arabic neologisms have the opportunity to take advantage of the existing conceptual framework and move the subject to a better point. In this study, the neologisms in the Al-Jazeera news site were taken as basis by using the concepts mentioned. The identified neologisms were examined from different perspectives and the current neologism status of Arabic was tried to be revealed. In the study, neologies were examined in terms of thematics and formation methods. Accordingly, neologisms in the fields of technology, politics, and social development are included. Six methods have been identified in the formation of neologies. By supporting these methods with examples, the tendency of Arabic to derive new words has been tried to be revealed. This study is based on the lexicography approach, which accepts new expressions that have not entered the dictionary. Accordingly, the neologisms given as examples in the study are expressions that are not included in the dictionary.